PERSEPSI PENGGUNA LAYANAN ANGKUTAN JASA KERETA API OLEH PT. KERETA API INDONESIA (PERSERO) DIVISI REGIONAL III PALEMBANG PROVINSI SUMATERA SELATAN - Nur Elly; Nadhya Nabila; Nelly Anggia Murni; Nirwana Nirwana; Novi Diana (Jurnal Ilmu Administrasi dan Studi Kebijakan (JIASK), 2021)
The problem that is used as the object of research is the perception of users of Railroad Transport Services by PT. Kereta Api Indonesia (Persero) Regional Division III Palembang. This research was conducted with the aim of analyzing the user's perception of Railroad Transport Services by PT. Kereta Api Indonesia (Persero) Regional Division III Palembang. In order to reveal and discuss the service performance which is the object of research, a qualitative research approach is used. This research approach is carried out with descriptive analysis method. The qualitative research approach was chosen with the consideration that qualitative research is a research method that focuses more on exploring the object of the problem in depth and dynamically according to the research subject as the party who knows, sees and feels directly the performance of the service. From the discussion of the results of the study, it was found that the perception of users of Railroad Transport Services by PT. Kereta Api Indonesia (Persero) Regional Division III Palembang, from the tangible dimension, PT. Kereta Api Indonesia (Persero) Regional Division III Palembang is revealed from the indicators of providing service counters, indicators of providing waiting rooms, and indicators of the number of service officers who have not fully met the expectations of the service recipients. In the dimension of reliability, the low perception of users of Railroad Transport Services by PT. Kereta Api Indonesia (Persero) Regional Division III Palembang. In the dimension of responsiveness, the low quality of service is revealed from the officers' response indicators to service recipient complaints, officers' response indicators to service recipients' criticism and officers' response indicators to the difficulties of service recipients who have not fully met the expectations of service recipients. In the Assurance dimension, the low quality of service is revealed from indicators of the ability of officers to serve, indicators of technical fluency of services and indicators of timeliness of services that have not fully met the expectations of service recipients. In the dimension of empathy, the low perception of users of rail transportation services by PT. Kereta Api Indonesia (Persero) Regional Division III Palembang is revealed from indicators of readiness of service officers, indicators of attention of service officers, and indicators of concern for service officers to complaints of service recipients who have not fully met the expectations of the service recipients, namely the users of rail transportation services by PT. Kereta Api Indonesia (Persero) Regional Division III Palembang.